Fusions of the lac and trp Regions of the Escherichia coli Chromosome - Miller, Jeffrey H. (1970)
Two classes of strains were studied in which the lac operon is transposed to a chromosomal site close to the tonB and trp loci. The two classes differ in the orientation of the lac region on the chromosome. In both types of strains, tonB mutants were selected in which deletions removing the tonB locus also caused a fusion of the lac and trp regions. The study of the properties of such fusion strains provides information on the control of both the lac and trp operons.